What Drives Customers to Choose Branchless Banking? An Empirical Study Using the Analytic Hierarchy Process - Eti Kusmiati; Nizar Alam Hamdani; Hanifah Fauziah; Dinar Mariam Kurniati; Melly C. Resmi (Khazanah Sosial, 2025)
This study aims to analyze customer preferences in choosing Branchless Banking services by examining various perceptions that influence their decision-making. The research focuses on four key factors: Perceived Ease of Use, Perceived Trust, Perceived Usefulness, and Perceived Risk. The Branchless Banking services evaluated in this study include BRILink, Agen46, and Mandiri Agen, platforms developed by major banks in Indonesia to expand financial services through agent-based networks. A mixed-methods approach was employed, combining quantitative analysis using the Analytic Hierarchy Process (AHP) and the Expert Choice software with qualitative insights to enrich the interpretation of results. Data were collected from 100 respondents with experience using all three services, ensuring a relevant and comprehensive evaluation. The findings reveal that Perceived Ease of Use is the most dominant factor influencing customer choice, with a weight of 39.40%, followed by Perceived Usefulness at 23.90%. Trust ranked third at 22.30%, while Risk had the lowest weight at 14.30%. Further analysis indicates that BRILink is the most preferred branchless banking service, scoring the highest (45.5%) across all criteria: Perceived Ease of Use, Perceived Usefulness, Trust, and Risk. These results suggest that BRILink aligns best with customer expectations across the evaluated dimensions. The study offers strategic insights for financial institutions to enhance agent banking services through a customer-centric approach.